The experience era is upon us - Jason Wolf (The Beryl Institute, 2016)
In this moment in healthcare, the challenges for those in the system are dynamically shifting and the perspectives, desires and needs of the healthcare consumer are putting positive and lasting pressures on how healthcare works that will shift healthcare from where it has been to where it must go. At the heart of this transition are the ideas framing an experience era, where collaborative, consumer-focused and purposeful actions can and will lead to a healthcare system returning to its fundamental calling, that of human beings caring for human beings. In doing so we can change the nature of healthcare and reignite the purpose that brought people to this work and that have individuals seek it for care. In this framing is also the call to action to contribute new insights and perspectives to expand the dialogue, reinforcing the critical and lasting nature of the experience conversation for all it has influenced and all it will impact for many years to come.